A Field Theory-Based Novel Algorithm for Navigational Hazard Index - Yihua Liu; Yu Ma (Journal of Marine Science and Engineering, 2023)
Collision risk assessment is crucial for autonomous ships to identify risks and make decisions for collision avoidance. In this paper, a field theory-based navel algorithm is proposed to define and describe the risk of ship collision. Based on the field theory and the asymmetric Gaussian function, the ship collision risk field is constructed, and the field potential is used to characterize the navigational hazard index. The effectiveness and superiority of the algorithm are verified through study cases. The results show that the proposed algorithm can obtain the index continuously, reflect the risk level accurately, and provide reliable basis for the navigation of autonomous ships. Therefore, it has important application potential in the development of intelligence navigation.